# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {2 x y}{3 x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}+\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {y^{2}-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y+\left (2 \sqrt {x y}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \ln \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x +2 y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x +y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x +\frac {y}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y-2}{y-x -4}
\] |
✓ |
✓ |
|
\[
{}2 x -4 y+6+\left (x +y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y-x +5}{2 x -y-4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {4 x +3 y+15}{2 x +y+7}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +3 y-5}{-y+x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \left (y+2\right )^{2}}{\left (x +y+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x +y+1-\left (4 x +2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -y-1+\left (y-x +2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +4 y\right ) y^{\prime } = 2 x +3 y-5
\] |
✓ |
✓ |
|
\[
{}y+2 = \left (2 x +y-4\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (y^{\prime }+1\right ) \ln \left (\frac {x +y}{x +3}\right ) = \frac {x +y}{x +3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -2 y+5}{y-2 x -4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x -y+1}{2 x +y+4}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+\left (x^{2} y^{4}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } \left (x -y^{2}\right )+y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} \left (y^{\prime }-x \right ) = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime } = y^{3}+x y
\] |
✓ |
✓ |
|
\[
{}y+x \left (2 x y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+x = 4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-\frac {2}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = y^{2} \sqrt {x -x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}\frac {2 x y y^{\prime }}{3} = \sqrt {x^{6}-y^{4}}+y^{2}
\] |
✓ |
✓ |
|
\[
{}2 y+\left (1+x^{2} y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x y+1\right )+x \left (1-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1+x^{2} y^{2}\right )+\left (x^{2} y^{2}-1\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-y^{4}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1+\sqrt {x^{2} y^{4}-1}\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \left (2-9 x y^{2}\right )+y \left (4 y^{2}-6 x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{x}+\left (y^{3}+\ln \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3+\left (2 y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +4 y+\left (2 x -2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}+4 x +2}{2 y-2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 \sqrt {x y} = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y-1}{x -y+3}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+y+\left (x -2 \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x +\frac {6}{y}+\left (\frac {x^{2}}{y}+\frac {3 y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y^{2}-x y = 0
\] |
✓ |
✓ |
|
\[
{}x +y-\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2 x}+\frac {x^{2}}{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {2}{t}+\frac {y}{t}+\frac {y^{2}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t}-1-y^{2}
\] |
✓ |
✓ |
|
\[
{}y+\sqrt {x^{2}+y^{2}}-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1+x^{2} y^{2}\right )+\left (x^{2} y^{2}-1\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{2} x^{3}-y+\left (2 x^{2} y^{3}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{y}+\sec \left (\frac {y}{x}\right )-\frac {x y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}\phi ^{\prime }-\frac {\phi ^{2}}{2}-\phi \cot \left (\theta \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (\phi ^{\prime }-\frac {\phi ^{2}}{2}\right ) \sin \left (\theta \right )^{2}-\phi \sin \left (\theta \right ) \cos \left (\theta \right ) = \frac {\cos \left (2 \theta \right )}{2}+1
\] |
✓ |
✓ |
|
\[
{}y \,{\mathrm e}^{x y}+x \,{\mathrm e}^{x y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 x y+{\mathrm e}^{y}+\left (y-x^{2}+x \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \sqrt {x^{2}-y^{2}}\, y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime }+y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \sin \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+5 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = x^{2}+x
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime }+y = 2 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = {\mathrm e}^{i x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+i y = x
\] |
✓ |
✓ |
|
\[
{}L y^{\prime }+R y = E
\] |
✓ |
✓ |
|
\[
{}L y^{\prime }+R y = E \sin \left (\omega x \right )
\] |
✓ |
✓ |
|
\[
{}L y^{\prime }+R y = E \,{\mathrm e}^{i \omega x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+a y = b \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 3 x^{3}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \,{\mathrm e}^{x} = 3 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\tan \left (x \right ) y = {\mathrm e}^{\sin \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = {\mathrm e}^{-\sin \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = b \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+x}{y-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{x -y}}{1+{\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y^{2}-4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|